Sentinel European Node Trial (SENT): 3-year results of sentinel node biopsy in oral cancer. Issue 18 (December 2015) - Schilling, Clare; Stoeckli, Sandro J.; Haerle, Stephan K.; Broglie, Martina A.; Huber, Gerhard F.; Sorensen, Jens Ahm; Bakholdt, Vivi; Krogdahl, Annelise; von Buchwald, Christian; Bilde, Anders; Sebbesen, Lars R.; Odell, Edward; et al.
Abstract: Purpose: Optimum management of the N0 neck is unresolved in oral cancer. Sentinel node biopsy (SNB) can reliably detect microscopic lymph node metastasis. The object of this study was to establish whether the technique was both reliable in staging the N0 neck and a safe oncological procedure in patients with early-stage oral squamous cell carcinoma. Methods: An European Organisation for Research and Treatment of Cancer-approved prospective, observational study commenced in 2005. Fourteen European centres recruited 415 patients with radiologically staged T1–T2N0 squamous cell carcinoma. SNB was undertaken with an average of 3.2 nodes removed per patient. Patients were excluded if the sentinel node (SN) could not be identified. A positive SN led to a neck dissection within 3 weeks. Analysis was performed at 3-year follow-up. Results: An SN was found in 99.5% of cases. Positive SNs were found in 23% (94 in 415). A false-negative result occurred in 14% (15 in 109) of patients, of whom eight were subsequently rescued by salvage therapy. Recurrence after a positive SNB and subsequent neck dissection occurred in 22 patients, of which 16 (73%) were in the neck and just six patients were rescued. Only minor complications (3%) were reported following SNB. Disease-specific survival was 94%. The sensitivity of SNB was 86% and the negative predictive value 95%. Conclusion: These data show that SNB is a reliable and safe oncological technique for staging the clinically N0 neck in patients with T1 and T2 oral cancer. EORTC Protocol 24021: Sentinel Node Biopsy in the Management of Oral and Oropharyngeal Squamous Cell Carcinoma. Highlights: Sentinel European Node Trial is the largest cohort of oral squamous cell carcinoma patients to undergo sentinel node biopsy (SNB) as a staging tool for elective neck dissection. Twenty-three percent of patients had occult metastasis detected by SNB. In all, 85% of patients with positive sentinel node had no further metastatic nodes on neck dissection. In 12.4%, a sentinel node was detected in the neck contralateral to the tumour. Sentinel node status significantly affected overall survival at 3 years (p = 0.00013).